Studies in Finishing Effects of Clay Mineral in Polymers and Synthetic Fibers - Faheem Uddin (Advances in Materials Science and Engineering)
The use of clay mineral in modifying the properties of polymeric material is improved in application. The current interest in modifying the polymeric materials, particularly polyethylene, polypropylene, polystyrene, and nylon using clay mineral for improved flame retardancy, thermal stability, peak heat release rate, fracture, and strength properties generated significant research literature. This paper aims to review some of the important recent modification achieved in the performance of polymeric materials using organoclay mineral. Degradation of clay mineral-polymer (nm) composite is discussed with appropriate known examples. Clay mineral (nm) loading of 5 wt.% to 7 wt.% that was significantly smaller than the percent loading of conventional fillers in polymeric materials introduced significant improvement in terms of thermal and physical stability. An attempt is made to emphasize flammability and thermal stability and to indicate the areas that are relatively little explored in modification of fiber-forming polymers to enhance further research interest.